Methodology For Compiling And Solving Methodological Issues On Topics (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The article reveals the most important conditions for solving problematic education and issues in chemistry lessons to increase the effectiveness of the educational process in higher educational institutions.